Unsere Kunsthalle : 30 Bilder für Kinder : Ausgewählte Werke der Staatlichen Kunsthalle Karlsruhe. - Staatliche Kunsthalle, Karlsruhe (Karlsruhe : Staatliche Kunsthalle, 1988)
Bonnard, Pierre ; Kirchner, Ernst Ludwig ; Kandinsky, Wassily ; Delaunay, Robert ; Heckel, Erich ; Macke, August ; Kanoldt, Alexander ; Nolde, Emil ; Dix, Otto ; Hubbuch, Karl ; Dubuffet, Jean ; Tàpies, Antoni
boek